An MDT-based rapid assessment method for the spatial distribution of trafficable sections of roads hit by earthquake-induced landslides - Bai, Xianfu; Dai, Yuqian; Zhou, Qingyun; Yang, Zhiquan (Frontiers in Earth Science, 2023)
In mountainous areas, roads are often damaged by earthquake-induced landslides (EL). The degree of road damage and the existing functional state will have a very important impact on the whole earthquake relief work. However, this question has long been plaguing scientists engaged in the earthquake disaster risk assessment. To solve this problem, an MDT-based rapid assessment method for the spatial distribution of trafficable sections of roads (TSR) hit by EL is proposed. It is employed to calculate the road trafficability. The spatial distribution of TSR is mapped. The method mainly consists of three procedures: a) Demarcate the road sections in the evaluated region; b) Create the data for earthquake-induced landslide sensitivity level for the evaluated region; c) Use the sample data to devise the MDT model for the TSR hit by EL and calculate the trafficability of road sections. This method was applied in the study of the 2008 Wenchuan Ms 8.0, the 2014 Ludian Ms 6.5, the 2012 Yiliang Ms 5.6 and Ms 5.7 earthquake-stricken regions. Among them, the case of Wenchuan earthquake was adopted to establish the rapid assessment method for the spatial distribution of TSR and to evaluate the efficacy of the method. The cares of Ludian and Yiliang were used to evaluate whether the method could be transplanted into similar regions. The p-value and the kappa coefficient were used to test and evaluate the significance and the consistence of the actual situation. The computed P-value for the Wenchuan study area was less than 0.001(just 2.52×10 -203 ) and the kappa coefficient was 0.91. This suggests that the computed TSR values are good indicators of blocked-road occurrences. In the Ludian-Yiliang study area, the computed P-value was less than 0.001 too (just 9.7×10 -107 ) and the kappa coefficient was 0.81. The results from the Ludian-Yiliang evaluated area showed that the method could be applied to similar regions.